Helen Keller - Davidson, Margaret 1936-; Watson, Wendy (New York Scholastic Inc, 1969)
A biography stressing the childhood of the woman who overcame the handicaps of being blind and deaf
American Corner
11
NEW_DMN_GN
Keywords: Keller, Helen -- 1880-1968; Blind; Deaf